Optimalisasi Operasi Mesin Cetak Pelet MKS-PLT15 Menggunakan Lagrange - Suzantry Handayani, Yanolanda; Haidi, Junas; Kurniawan, Adhadhi; Alqap, Sofwan (Electrician : Jurnal Rekayasa dan Teknologi Elektro, 2022)
Bengkulu Province from Kaur Regency to Moko-Moko Regency is directly adjacent to the Indian Ocean. So that many Bengkulu residents are fishermen and farmers. Of course, with abundant natural resources, there are some fish and agricultural products that have not been utilized optimally, for example, young fish on Bai Island which are still widely discarded and milled rice bran which is very cheap. On the other hand, there is a very big problem experienced by farmers or breeders in Bengkulu Province, namely the price of fish and poultry feed is very high, thus making fish and poultry farmers unable to survive because of the high cost of feed. To reduce the production cost of making pellets, a research was carried out on optimizing the operation of the pellet molding machine Type MKS-PLT 15 with dimensions of 340 x 150 x 325 mm, the power used was 450 watts and the voltage used was 220 v / 50 Hz. The research carried out looked at the machine operation at 25 percents, 50 percents, 75 percents and 100 percents, from the results of the research that had been carried out, it was found that the 25 percents machine operation cost of 6mm pellet printing was 0.00762 kwh/kg or Rp. 11.021/kg, machine operation 50 percents production cost 0.009901kwh/kg or Rp. 14.3039/kg machine operation 75 percents pellet production cost 0.01235kwh/kg or Rp. 17.842/kg while the machine operation is 100 percents pellet production cost of 0.01084 kwh/kg or Rp. 15.6605/kg. so that from the research carried out, it was found that the operation of the MKS-PLT15 pellet machine, the low production cost, was in machine operation 0-50 percents of the capacity of the pellet machine's ability to operate.